Deformations of Noncompact Calabi-Yau threefolds (2018)
We describe deformations of noncompact Calabi-Yau threefoldsWk := Tot(OP1 (-k) ⊕ OP1 (k - 2)),for k = 1, 2, 3. We compute deformations concretely by calculations of the cohomology group H1(Wk, TWk) via Čech cohomology. We show that for each k = 1, 2, 3 the associated structures are qualitatively different, and we also comment on their differences from the analogous structures of simpler non-compact twofolds Tot(OP1 (-k)).